2020
DOI: 10.11622/smedj.2020016
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, confidence and attitude of primary care doctors in managing in-flight medical emergencies: a cross-sectional survey

Abstract: INTRODUCTION Medical emergencies occur at a rate of one in 604-753 flights. Doctors travelling on commercial flights may encounter an in-flight medical emergency requiring their assistance. There is a paucity of studies on how confident primary care doctors are in managing in-flight medical emergencies. This study aimed to determine the knowledge, confidence and attitude of primary care doctors in managing in-flight medical emergencies. METHODS A cross-sectional study was conducted on all primary care doctors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Moreover, the vast majority of participants in our study reported that they will identify themselves as doctors in the event of IMEs. This finding agreed with a study among 182 primary health care physicians in Malaysia which reported that about 70% of participants were willing to help during IMEs [3].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the vast majority of participants in our study reported that they will identify themselves as doctors in the event of IMEs. This finding agreed with a study among 182 primary health care physicians in Malaysia which reported that about 70% of participants were willing to help during IMEs [3].…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that nearly half of the participants were concerned about the medico-legal implications which may arise from their assistance in IMEs. This was lower than reported by Ng et al among 182 primary care doctors in Malaysia in which 62.6% of participants were afraid and 21.4% were unsure of the medico-legal consequences of their help in such a condition [3]. A physician who volunteers to provide medical assistance creates a doctor-patient relationship, and with it comes its obligations and liability risk.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…While stratifying patients by the acuity of their needs is important, understanding the level of knowledge and confidence of primary care doctors in managing various medical urgencies is also crucial in the delicate balance to right-site patients. Meanwhile, Ng et al (4) highlighted a lack of confidence among primary care doctors in Kuala Lumpur when managing in-flight emergencies, suggesting that building primary physicians' confidence and improving their management of common medical conditions would address some of the gaps we currently face. By reducing inappropriate attendances and allowing ED physicians to focus on the sickest patients, Ibrahim et al (5) demonstrated in their work on acute aortic dissection that we can better target our resources so as to minimise the occurrence of missed diagnoses among critically ill patients.…”
mentioning
confidence: 99%